Pembagian Peran Suami dan Istri dalam Membangun Rumah Tangga Sakinah Menurut Syekh Nawawi Al-Bantani - Fahmi, Zulkifli Reza (Qanun: Jurnal Hukum Keluarga Islam, 2023)
Husband and wife in the household have their respective duties and roles in creating the goals of marriage, namely sakinah mawaddah and rahmah. However, lately many households have found it difficult to create and realize the goals of the marriage. This happened allegedly due to a lack of knowledge on the part of the wife and husband regarding their roles and duties in the household. One of the Indonesian ulama who has an interesting multidisciplinary scientific capacity to study is Syekh Nawawi Al-Bantani. Where he also concentrated on discussing munakahat fiqh to the point where he wrote the books Uqudul-lujjain and Nihayatu-z-Zain. In this study used a qualitative method with a library research approach. Researchers use descriptive methods to parse, interpret and analyze data. From the results of this study it was found that according to Sheikh Nawawi the rights and obligations of husband and wife are very important to understand in order to know the roles and duties of each in building a happy family of sakinah mawaddah wa rahmah as the goal and vision of marriage. In this division refers to the rights and obligations of husband and wife. On this basis, the husband's role is as a leader or head of the household, breadwinner, educator and teacher for his wife. Meanwhile, the wife's role is as a husband's companion who must obey except in disobedience, household managers, and husband's partners in achieving life goals.